Pediatric Adrenal Insufficiency: Diagnosis, Management, and New Therapies - Bowden, Sasigarn A. (Int J Pediatr, 2018)
Adrenal insufficiency may result from a wide variety of congenital or acquired disorders of hypothalamus, pituitary, or adrenal cortex. Destruction or dysfunction of the adrenal cortex is the cause of primary adrenal insufficiency, while secondary adrenal insufficiency is a result of pituitary or hypothalamic disease. Timely diagnosis and clinical management of adrenal insufficiency are critical to prevent morbidity and mortality. This review summarizes the etiologies, presentation, and diagnosis of adrenal insufficiency utilizing different dynamic hormone testing and describes current treatment recommendations and new therapies.